DAMPAK KAPABILITAS DAN MOTIVASI TERHADAP KOMITMEN DAN KINERJA DOSEN - Titik Ngasmiati (Jurnal Riset Bisnis Indonesia, 2013)
This study aims to examine the influence of capabilities, motivation, commitment and satisfactionwith the performance of the lecturers. In addition, this study is also aimed to examine the influenceof motivation and commitment to the job satisfaction of lecturers. The research was conducted at theFaculty of Engineering, Diponegoro University Semarang. Total population is 480 lecturers. Basedon Slovin formula with 10% degree of precision, the minimum total sample is 88 lecturers. The studywas conducted by survey method by distributing questionnaires to 125 lecturers with a purposivesampling method. Answer questionnaires returned and qualified were 92 pieces. The analysis tehniqueusing Partial Lease Square (PLS).The results showed that the capability, motivation, commitmentand satisfaction significantly influence the performance of lecturers. Motivation and commitmentto significantly affect job satisfaction. Based on these results the performance of the lecturers ofthe Faculty of Engineering, Diponegoro University Semarang can be improved by increasing thecapabilities, motivation, and increasing the commitment of the lecturers, implementation of jobsatisfaction.Keywords: lecturer performance, capabilty, motivation, commitment, job satisfaction